The use of smartphones on General Internal Medicine wards - Tran, K.; Morra, D.; Lo, V.; Quan, S.; Wu, R. (Applied Clinical Informatics, 2014)
Objective: To describe the uses of institutional and personal smartphones on General Internal Medicine wards and highlight potential consequences from their use.Methods: A mixed methods study consisting of both quantitative and qualitative research methods was conducted in General Internal Medicine wards across four academic teaching hospitals in Toronto, Ontario. Participants included medical students, residents, attending physicians and allied health professionals. Data collection consisted of work shadowing observations, semi-structured interviews and surveys.Results: Personal smartphones were used for both clinical communication and non-work-related activities. Clinicians used their personal devices to communicate with their medical teams and with other medical specialties and healthcare professionals. Participants understood the risks associated with communicating confidential health information via their personal smartphones, but appear to favor efficiency over privacy issues. From survey responses, 9 of 23 residents (39%) reported using their personal cell phones to email or text patient information that may have contained patient identifiers. Although some residents were observed using their personal smartphones for non-work-related activities, personal use was infrequent and most residents did not engage in this activity.Conclusion: Clinicians are using personal smartphones for work-related purposes on the wards. With the increasing popularity of smartphone devices, it is anticipated that an increasing number of clinicians will use their personal smartphones for clinical work. This trend poses risks to the secure transfer of confidential personal health information and may lead to increased distractions for clinicians.Citation: Tran K, Morra D, Lo V, Quan S, Wu R. The use of smartphones on General Internal Medicine wards: A mixed methods study. Appl Clin Inf 2014; 5: 814–823http://dx.doi.org/10.4338/ACI-2014-02-RA-0011
Keywords: Smartphone; communication; clinician; healthcare